PEMBELAJARAN VOKAL TINGKAT DASAR DI GEORAMA YAMAHA MUSICSCHOOL - Zellika, - (2015)
Research about basic vocal learning at Georama Yamaha Music School came from the curiousity of writer of learning curiculum at Yamaha Music School that adjusted to age, physical and mental development in general which means to sent the subject by what has been managed in general of vocal and music. The reason why the basic vocal learning chosen is because the writer's ability that has learn about Instrumen Pilihan Wajib Vokal Barat in Departemen Pendidikan Seni Musik, UPI. Based on that things has become a problem lists which has been the study of this thesis which was the subject options, learning methods and results of the basic vocal learning at GYMS. The purpose is to discussed the subject options, how to implemented the learning method and the results of the basic vocal learning by the learning process at GYMS. To gets the study based on the problem lists writer will do a research with analysis descriptive method with qualitative approached. This method chosen because to related by the problem lists that has been written. The point of this thesis is about study of subjects, learning method and results of basic vocal learning at GYMS. The learning activity that just has short duration and song choice which has the hard level has become one of the study by this research.